Analisis Yuridis Normatif atas Pemanfaatan Cukai Minuman Berpemanis Dalam Kemasan (MBDK) untuk Pembiayaan Program Jaminan Kesehatan Nasional oleh BPJS Kesehatan (Lembaga Pengembangan Kinerja Dosen, 2025)
The National Health Insurance (JKN) system is a strategic program of the Indonesian government to ensure equitable access to healthcare services for all citizens. However, the sustainability of JKN financing faces challenges due to rising healthcare costs, particularly from non-communicable diseases (NCDs). One potential solution is to utilize fiscal instruments such as excise taxes, especially on sugar-sweetened beverages (SSBs), which are known to contribute significantly to the burden of NCDs. This study aims to analyze the legal framework and urgency of utilizing excise revenues from sugar-sweetened beverages (SSBs) to support JKN financing. Using a normative juridical method and a statutory, conceptual, and comparative approach, this research explores relevant laws and public health data. The findings reveal that although the allocation of excise on SSBs for JKN is not yet explicitly regulated, the existing legal framework—particularly the pattern of cigarette tax and tobacco excise revenue allocation—provides a strong precedent. From a medical perspective, high SSBs consumption has been shown to increase the risk of NCDs, placing a significant burden on JKN. Therefore, implementing MBDK excise not only aligns with public health goals but also holds fiscal potential to support sustainable healthcare financing.